2016
DOI: 10.1149/2.0981603jes
|View full text |Cite
|
Sign up to set email alerts
|

Pt Sub-Monolayer on Au: System Stability and Insights into Platinum Electrochemical Dissolution

Abstract: Platinum is the best single element oxygen reduction reaction electrocatalyst. In recent years, several advanced catalysts have been suggested. One of them is the so-called “platinum monolayer electrocatalyst”. In this work we demonstrate the potential- and time-resolved dissolution characteristics of such sub-monolayer platinum supported on gold in potentiodynamic and potentiostatic regimes. It is shown that the as-prepared Pt@Au is not stable, but rather shows significant dissolution of both Pt and Au simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
4
32
0
Order By: Relevance
“…Similarly, Cherevko et al showed that the onset of Pt dissolution after intermixing shift to slightly higher potential than those of the pure elements. 73 Furthermore, in line with the oxide reduction peak shift (Fig. 1), the cathodic Pd dissolution of the alloyed material ends significantly earlier, one more time confirming a correlation between Pd-oxide reduction and cathodic dissolution processes.…”
Section: Catalysis Science and Technology Papersupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly, Cherevko et al showed that the onset of Pt dissolution after intermixing shift to slightly higher potential than those of the pure elements. 73 Furthermore, in line with the oxide reduction peak shift (Fig. 1), the cathodic Pd dissolution of the alloyed material ends significantly earlier, one more time confirming a correlation between Pd-oxide reduction and cathodic dissolution processes.…”
Section: Catalysis Science and Technology Papersupporting
confidence: 64%
“…72 Recently, however, Cherevko et al showed that a Pt sub-monolayer on bulk Au is not stable, but rather shows significant dissolution of both Au and Pt similar to the pure polycrystalline elements. 73 In our case, the Au and Pd dissolved masses in the alloy normalized by the nanoparticle total surface area (insets in Fig. 2A and B) are in absolute terms approximately half of those for the pure metals (for Pd ≈ 60%, for Au ≈ 50%).…”
Section: Dissolution Onset Potentialmentioning
confidence: 50%
“…Representative is the utilization of SFC‐ICP‐MS with gradient composition libraries ( e. g. Pt 1−x Cu x for ORR and Ir 1−x Ru x for OER) for which high‐throughput activity and stability screening can be achieved. On‐line ICP‐MS is also indispensable when it comes to multielemental analysis, allowing simultaneous quantification of, e. g. Pt and Cu or Ir and Ru from the gradient libraries presented above, or Pt and Au from sub‐monolayer Pt covered Au, etc. Traditional techniques like rotating ring disk electrode (RRDE) or electrochemical quartz crystal microbalance (EQCM) fail in this.…”
Section: Basic Principles Of On‐line Icp‐ms Operationmentioning
confidence: 99%
“…Overall, the best choice of both ion concentrations would keep the fraction of electrodeposited growing metal lower than 1% during UPD layer formation [59]. The one-cell approach is very attractive with its operational simplicity and when applicable has been used by many groups for the purposes of fundamental or applied research involving SLRR deposition [60][61][62]. It ensures best efficiency in comparison with the shuttling and flow-cell methods as neither changes of electrolytes/water nor exposure to the environment ever take place in the one-cell deposition configuration.…”
Section: The One-cell Approachmentioning
confidence: 99%